Does marriage explain murders in a society? In what way is divorce a public health concern? - Bourne, P.A.; Hudson-Davis, A.; Sharpe-Pryce, C.; Clarke, J.; Solan, I.; Rhule, J.; Francis, C.; Watson-Coleman, O.; Sharma, A.; Campbell-Smith, J.; Allen, T. (International Journal of Emergency Mental Health, 2014)
Introduction: Like medicine, public health practitioners seek to understand causes of mortality, practices of humans and issues that can change population conditions, in order to preserve and care for life. The murder pandemic has been such in Jamaica that the World Bank sponsored a qualitative study on crime in urban areas in Jamaica in the late 1990s to provide a platform to guide policy intervention and programmes. As a result this study will fill the gap in the literature by providing the evidence to support that divorce and marriage are public health concerns from the perspective of murders. Objective: To evaluate the role of divorce and marital relationships on murders. Materials and methods: The data for this study are taken from various Jamaica Government Publications. The period for this work is from 1950 through 2013. Data were recorded, stored and retrieved using the Statistical Packages for the Social Sciences (SPSS) for Windows, Version 21.0. The level of significance that is used to determine statistical significance is less than 5% (0.05). Ordinary least square (OLS) regression analyses and curve estimations were used to determine models and best fitted models. Results: On average, annually, 523 Jamaicans are murdered (± 484), with there being 9,531 marriages (±22,747) and 904 divorces (±468). Logged marriage rate and divorce rate are factors of murder rate, with both independent factors accounting for 82.2% of the variability in the murder rate. Both factors are positively correlated with the murder rate, with the divorce rate accounting for most of the variance in the murder rate (R2 = 79.2%). Conclusion: Death can be extremely devasting to families, however, murder among married couples can severely disrupt the lives of both families along with any children from such relationship. © 2014, Chevron Publishing Corporation. All rights reserved.
1 citations (Crossref) [2023-10-31]
Keywords: Adult; Deaths; Divorce; Female; Homicide; Homicides; Humans; Jamaica; Jamaican; Male; Marital relationship; Marriage; Mortality; Murder; Partner-homicides; Public Health; Public health; Sexual relationship; adult; child; clinical study; death; dept.pch; divorce; epidemiology; family; female; genetic polymorphism; government; homicide; human; least square analysis; male; marriage; married person; mortality; public health; sociology; statistical significance; statistics and numerical data

Recruitment and retention of healthy and high-risk older adults for a multiyear influenza vaccination study - Dill, J.; Unson, C.; Kenyon-Pesce, L.; Kuchel, G.A.; McElhaney, J. (Connecticut Medicine, 2014)
Purpose: Evaluate five different recruitment strategies for their capacity to enroll and retain both healthy and vulnerable older adults as part of a multiyear influenza vaccination study. Methods: We analyzed recruitment methods and other characteristics of individuals who participated in or were considered for five sequential one-year studies. Results: Of 940 screened individuals, 820 met eligibility criteria with 795 enrolled over the five-year study (307 primary participants). Among these enrollees, 63.4% were female and 95.5% were white, with mean ages of 75.3 (older group) and 30.6 (younger group). More than a half (56.7%) of the participants enrolled more than once, participating an average of 2.56 (SD=1.6) times. The majority (81.9%) of individuals recruited each year were return participants identified during earlier recruitments. Physician referrals resulted in only 5.3% recruitments. Conclusions: Recruitment and retention of study subjects, especially older adults, was facilitated by the existence of a database listing past participants.
Keywords: Adult; Advertising as Topic; Aged; Databases as Topic; Electronic Mail; Female; Humans; Influenza Vaccines; Influenza; Human; Male; Middle Aged; Patient Selection; Postal Service; Referral and Consultation; Vaccination; adult; advertizing; aged; article; data base; dept.pch; e-mail; female; human; influenza; influenza vaccine; male; middle aged; patient referral; patient selection; postal mail; vaccination; ⛔ No DOI found

Stress, stigma, and sexual minority status: the intersectional ecology model of LGBTQ health - Mink, Michael D; Lindley, Lisa L; Weinstein, Ali A (Journal of Gay and Lesbian Social Services, 2014)
One of the four overarching goals of Healthy People 2020 is to achieve health equity, eliminate health disparities, and improve the health of all groups, including the health of lesbian, gay, bisexual, transgender, and questioning (LGBTQ) populations. In 2011, the Institute of Medicine (IOM) released a report that drew attention to the unique health disparities experienced by sexual minorities and underscored the need for a comprehensive approach to sexual minority health research. This article proposes a new model of LGBTQ health to help measure, explore, explain, and predict the impact of sexual minority status on health outcomes. The Intersectional Ecology Model of LGBTQ Health (IEM) demonstrates how the relentless hypervigilance of LGBTQ individuals in a heteronormative society impacts health outcomes through the primary vehicles of stigma and chronic, elevated stress. The purpose of the IEM is to guide future research and enhance public health practice for LGBTQ populations. © 2014 Taylor & Francis Group, LLC.
76 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-461-624-141-749 tex.type: [object Object]
Keywords: LGBTQ health; dept.pch; health ecology model; sexual and gender minority health; social context; stigma; stress cycle